Copper(II) and Platinum(II) Naproxenates: Insights on Synthesis, Characterization and Evaluation of Their Antiproliferative Activities - Amanda A. Silva; Silmara C. L. Frajácomo; Állefe B. Cruz; Kaio Eduardo Buglio; Daniele Daiane Affonso; Marcelo Cecconi Portes; Ana Lúcia T. G. Ruiz; João Ernesto de Carvalho; Wilton R. Lustri; Douglas H. Pereira; Ana M. da Costa Ferreira; Pedro P. Corbi (Inorganics, 2023)
The growth of antibiotic resistance is a matter of worldwide concern. In parallel, cancer remains one of the main causes of death. In the search for new and improved antiproliferative agents, one of the strategies is the combination of bioactive ligands and metals that are already consolidated in the synthesis of metallopharmaceutical agents. Thus, this work deals with the synthesis, characterization, and study of naproxen (Nap)-based complexes of copper(II) and platinum(II) as antiproliferative agents. The copper complex (Cu–Nap) presents a binuclear paddle-wheel structure in a 1 Cu:2 Nap:1 H2O molar composition, in which Cu(II) is bonded to the carboxylate oxygens from naproxenate in a bidentate bridging mode. The platinum complex (Pt–Nap) was identified as the square planar cis-[Pt(Nap)2(DMSO)2] isomer, in which Pt(II) is bonded to the carboxylate oxygen atom of Nap in a monodentate fashion. Both complexes were inactive against the Gram-positive and Gram-negative bacterial strains assessed. Pt–Nap presented low cytostatic behavior over a set of tumor cells, but good viability for normal cells, while Cu–Nap was cytotoxic against all cells, with a cytocidal activity against glioma tumor cells.